From Convenience to Compulsion: Exploring the Economic Dynamics of E-Wallet-Induced Impulse Buying Among Gen Z in Indonesia - Yasmin, Khoirunnida; Setyaning, Alldila (International Journal of Economics Development Research (IJEDR), 2025)
This study investigates the economic dynamics behind impulse buying behavior induced by e-wallet usage among Generation Z in Indonesia. Applying the Stimulus-Organism-Response (S-O-R) framework, the research explores how perceived interactivity, perceived risk, visual appeal, and subjective norms influence user satisfaction and perceived enjoyment—two key psychological mediators that drive impulsive purchase decisions. The economic implications of these psychological factors are considered in the context of increased digital financial accessibility and consumer spending behavior. A total of 325 valid responses were obtained through a structured questionnaire and analyzed using Structural Equation Modeling (SEM) via SmartPLS v.3.0. The findings reveal that perceived interactivity, visual appeal, and subjective norms significantly enhance user satisfaction and perceived enjoyment. However, perceived risk shows no significant impact on these mediators. Notably, while user satisfaction does not lead to impulse buying, perceived enjoyment exerts a strong positive influence on such behavior. These insights highlight the critical role of digital economic convenience in shaping consumer spending habits, offering valuable implications for financial technology firms and marketers aiming to foster engagement and drive purchasing behaviors among Gen Z consumers.